2014
DOI: 10.1007/s10068-014-0219-9
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of EGCG through Inhibition of NADPH oxidase expression in endothelial cells

Abstract: Green tea extract and epigallocatechin gallate (EGCG) have been extensively used in functional foods because of their beneficial health effects. In this study, the mechanism responsible for EGCG-induced protective effects in endothelial cells was investigated. EGCG exposure significantly decreased mRNA expression of the inflammatory genes monocyte chemotactic protein-1 (MCP-1) and vascular cell adhesion molecule-1 (VCAM-1), and of the NADPH oxidase subunits p22phox and Nox2. In addition, EGCG reduced tumor nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A number of additional studies have also reported that EGCg and related polyphenols present in green tea affects SMCs proliferation via activating p53, by down regulating NF-κB, or by suppressing mitogen activated protein kinase pathway [ 63 , 64 ]. A study reported in the literature depicts that EGCg decreases oxidative stress and inflammation in ECs by reducing NADPH oxidase expression at the transcriptional level [ 65 ]. Our findings corroborate earlier observations reported by Han and co-workers [ 66 ], related to the effects of EGCg on ECs and SMCs migrations.…”
Section: Discussionmentioning
confidence: 99%
“…A number of additional studies have also reported that EGCg and related polyphenols present in green tea affects SMCs proliferation via activating p53, by down regulating NF-κB, or by suppressing mitogen activated protein kinase pathway [ 63 , 64 ]. A study reported in the literature depicts that EGCg decreases oxidative stress and inflammation in ECs by reducing NADPH oxidase expression at the transcriptional level [ 65 ]. Our findings corroborate earlier observations reported by Han and co-workers [ 66 ], related to the effects of EGCg on ECs and SMCs migrations.…”
Section: Discussionmentioning
confidence: 99%